UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKAN INTERAKSI SOSIAL SISWA DI SEKOLAH - Suryani, Rina; Sinaga, Ave Laura; Alzika, Efti; Agatha, Stefany Putri (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Social interaction is a reciprocal relationship between individuals and other individuals that occurs through communication and individual behavior in their environment. This study aims to determine the efforts that can be made by Guidance and Counseling Teacher to improve students' social interactions at school. The research method used is a narrative literature review on five references by taking from the Google Scholar database from 2019, 2023, and 2024. The results obtained from the research show that the Guidance and Counseling Teacher efforts to improve students' social interactions at school include (1) motivating students to behave well, (2) understanding and examining why they have to behave this way and then providing understanding and through imitation by modeling attitudes, (3) can be done by providing services, be it information services regarding social attitudes or individual counseling services, (3) can be done by providing services, be it information services on social attitudes or individual counseling services, and group counseling services according to the level of problems faced by students, (4) providing guidance, direction in solving various problems (5) collaborating with all personnel in the school so as to build self-potential, especially in learning (6) approaching students, (7) by compiling guidance and counseling programs, (8) implementing programs according to the needs of the problems they face with individual counseling services, group counseling and group guidance, (9) evaluating the implementation of the program, (10) analysis of the results and follow-up of the program that has been carried out.